TAX ACCOUNTING AND CORPORATE BEHAVIOR: A BIBLIOMETRIC ANALYSIS - Shkromyda , N.Ya. (The actual problems of regional economy development, 2025)
The article carries out a detailed bibliometric study aimed at studying the development of scientific discourse that combines the issues of tax accounting with the corporate behavior of taxpayers in the modern economic environment. The relevance of the topic is substantiated in view of the intensification of global challenges, the transformation of the regulatory space and the growth of the role of socially responsible business behavior. It is determined that accounting for taxes and payments under them serves not only as a technical tool of fiscal administration, but also as an element of strategic management that forms the image of the enterprise and reputational capital among stakeholders. The study uses the methodology of bibliometric analysis, which includes the analysis of public interest using Google Trends, the systematization of publication activity in the Scopus database, as well as the construction of scientometric maps using the VOSviewer software. The analysis showed an increase in scientific interest in the topic of tax accounting and corporate behavior, but revealed an insufficient level of methodological integration between accounting tools and behavioral approaches in the context of corporate business integrity. The results of the visualization allowed us to identify four dominant scientific clusters, which are concentrated around cost accounting, taxation in the interests of society, financial audit and tax legalization, as well as social responsibility and sustainable development. The geographical structure of publication activity indicates the leadership of the USA, China, Great Britain and other countries with a high level of institutional and cultural development. The study found that tax accounting in combination with behavioral characteristics of business forms a new interdisciplinary plane that requires further theoretical development, improvement of analysis tools and development of applied models. The development of accounting and analytical support is of particular importance, which would allow to adequately reflect not only tax obligations, but also responsible tax behavior of enterprises.